2023
DOI: 10.1093/icesjms/fsad160
|View full text |Cite
|
Sign up to set email alerts
|

Major shift in the copepod functional community of the southern North Sea and potential environmental drivers

M M Deschamps,
M Boersma,
C L Meunier
et al.

Abstract: Copepods form the bulk of secondary production in marine ecosystems and are a major resource for higher trophic levels. Copepods are highly sensitive to environmental changes as they are ectotherms with a short life span whose metabolism and development depend on abiotic conditions. In turn, changes in their functional structure (i.e. functional trait composition) can have impacts on ecosystems. We examined changes in the copepod functional community in the North Sea over the past five decades, using a trait-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…However, we found that the shifting baseline did not fully remove the temporal patterns and instead found a shift from the 1980s (characterized by only a few strong heatwaves) to the 1990-2007, which contained two of the three severe events and twice as many strong heatwaves per decade than any other period of the time series. The end of the decade of the 1980s and the 1990s was characterized by important changes in the Northern Hemisphere (Beaugrand et al 2015), including North Sea phytoplankton (Defriez et al 2016;Di Pane et al 2022) and zooplankton (Kirby et al 2007;Deschamps et al 2023). In the German Bight, the copepod assemblages shifted from a dominance of summer, long-lived herbivores to autumn, short-lived carnivores (Deschamps et al 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we found that the shifting baseline did not fully remove the temporal patterns and instead found a shift from the 1980s (characterized by only a few strong heatwaves) to the 1990-2007, which contained two of the three severe events and twice as many strong heatwaves per decade than any other period of the time series. The end of the decade of the 1980s and the 1990s was characterized by important changes in the Northern Hemisphere (Beaugrand et al 2015), including North Sea phytoplankton (Defriez et al 2016;Di Pane et al 2022) and zooplankton (Kirby et al 2007;Deschamps et al 2023). In the German Bight, the copepod assemblages shifted from a dominance of summer, long-lived herbivores to autumn, short-lived carnivores (Deschamps et al 2023).…”
Section: Discussionmentioning
confidence: 99%
“…The end of the decade of the 1980s and the 1990s was characterized by important changes in the Northern Hemisphere (Beaugrand et al 2015), including North Sea phytoplankton (Defriez et al 2016;Di Pane et al 2022) and zooplankton (Kirby et al 2007;Deschamps et al 2023). In the German Bight, the copepod assemblages shifted from a dominance of summer, long-lived herbivores to autumn, short-lived carnivores (Deschamps et al 2023). We cannot ascribe those changes to marine heatwaves; nutrients are hypothesized to have contributed to the change at least for phytoplankton (Di Pane et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Phosphate often dictates the growth of algae and other autotrophic organisms. Variations in feeding traits might be directly linked to how copepods exploit these resources, with herbivorous copepods particularly favored in environments where phosphate-induced algal blooms occur [70]. Conversely, species that primarily feed on microorganisms-located on the right side of the first axis-may be influenced by sulfate concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Plankton organisms form the base of pelagic marine food webs and are particularly sensitive to ecosystem changes. For instance, warming and changes in dissolved nutrient concentrations in coastal seas observed over the past decades have altered phytoplankton and zooplankton assemblages, marked by shifts in their taxonomic and functional structure, with consequences for the entire ecosystem such as nutrient turnover and fish recruitment (Alvarez-Fernandez et al, 2012;Capuzzo et al, 2018;Di Pane et al, 2022;Di Pane et al, 2023;Marques et al, 2023;Deschamps et al, 2023). However, less is known on how environmental changes could further impact coastal plankton communities, and especially on the combined impact of multiple drivers (Sommer et al, 2015;Garzke et al, 2016;Horn et al, 2020).…”
Section: Introductionmentioning
confidence: 99%